Women representation on boards: a South African perspective. Issue 2 (6th June 2016) - Willows, Gizelle; van der Linde, Megan
Abstract : Purpose: By looking at both theoretical and empirical findings, this study aims to investigate whether gender diversity results in improved corporate governance and financial performance for companies. Design/methodology/approach: An analysis of the board composition of the Johannesburg Securities Exchange Top 40 companies as at 30 June 2013 and a comparison of the financial performance of the company were conducted. Findings: Female directors were found to make up, on average, 18.78 per cent of the board of directors, with the majority of these women being in non-executive positions. Women representation appears to influence company performance positively when using accounting-based measures of performance (such as return on assets and return on equity), but negatively when using market-based measures (such as Tobin's Q). The critical mass concept is also assessed and is found to have a positive effect. Originality/value: These findings are of relevance to the boards of directors adhering to corporate governance requirements by challenging the role of women on the board of directors, as well as that of investors and those in practice, to understand the current status of women representation.